Self-Evaluation With SWOT Analysis and ANP in The Sharia Business Management Department - Maskuroh, Nihayatul; Suganda, Asep Dadan; Nurhayati, Siti (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2023)
This study aims to find out how the efforts of the Faculty of Economics and Islamic Business, UIN Sultan Maulana Hasanuddin Banten, in developing the Sharia Business Management (SBM) study program with all the strengths, weaknesses, and opportunities in dealing with various existing threats. This research uses a feasibility study method for the SBM program with quantitative SWOT analysis and the Analysis Network Process approach to formulate alternative strategies using Super Decisions software. Based on the data obtained, it can be concluded that the positioning of the Sharia Business Management study program, according to the respondents, is quite important and reaches a percentage of 56.5 with the argument that the mastery of Sharia-based business management is quite important as much as 50.8%. Meanwhile, from the Internal Factor Evaluation and External Factors Evaluation metrics, it can be seen that the position of the X axis is at point 3.60, and the position of the Y axis is at point 2.68. Therefore, because the meeting point between the X and Y axes is in quadrant I, so the strategy used is progressive (aggressive), namely maximizing the Strengths-Opportunities strategy by paying attention to other strategies such as Weakness-Opportunities, Strengths-Threats, and Weakness-Threats